Reformismo social em John R. Commons - Soares, Eduardo Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research aims to discuss aspects of the thought of John R. Commons regarding their engagement with the reform of capitalism. He focuses on his interpretation of the socioeconomic context of American capitalism, which led him to distance himself from the Marxist revolutionary praxis and the authoritarian reformism offered by the variant of European fascism. Based on extensive literature review, the research rebuild through a historical and theoretical context, his thinking and show the evolution of his ideas throughout his life. Recreating the terms in which Commons defended his reformist project, called him reasonable capitalism.

Esta pesquisa busca discutir aspectos do pensamento de John R. Commons relativo ao seu engajamento com a reforma do capitalismo. Ele foca sobre a interpretação desse autor do contexto socioeconômico do capitalismo norte-americano, que o levou a distanciar-se da práxis revolucionária marxista e do reformismo autoritário oferecido pela variante do fascismo europeu. Baseada em ampla revisão bibliográfica, a pesquisa reconstruirá através de uma, contextualização histórica e teórica, o seu pensamento e mostrará a evolução de suas ideias ao longo de sua vida. Recriando os termos nos quais Commons defendeu seu projeto reformista, chamado por ele de capitalismo razoável
Keywords: Commons, John R. (John Rogers) 1862-1945; Economia - História; Capitalismo; Capitalism